Floristic characteristics, social and ecosystem importance of coffee-based agroecosystems in the mountainous West of Côte d’Ivoire - Piba, Serge Cherry; Ta, Bi Irié Honoré; Karidioula, Tinnin Patricia; Tra, Bi Fezan Honora (Ethnobotany Research and Applications, 2025)
Background: In response to the reduction of forests in favor of monoculture cash crops in Côte d'Ivoire, agroecosystems have become an important resource for the daily lives of local populations and for biodiversity conservation in the Montagnes District an area overexploited by shifting agriculture. This study aims to contribute to the understanding and valorization of coffee ecosystems in the mountainous west. Methods: An ethnobotanical survey and floristic inventories were conducted from February to March 2024 in the Montagnes District, covering three departments (Man, Facobly, and Biankouma), within the coffee plantations of 27 reference farmers associated with the National Agronomic Research Center of Côte d’Ivoire. Floristic surveys documented the identity and abundance of each tree species associated with coffee plants, while semi-structured interviews identified their uses by coffee farmers. Results: In agrosystems, 431 trees associated with coffee plants were counted. These trees are distributed among 67 species, belonging to 54 genera and 22 botanical families. The predominant species, with lowest Rarefaction index (Ri), regardless of the department, were Albizia adiantifolia (Schum.) W.F.Wright (Ri: 22.22%) and Albizia zygia (DC.) J.F.Macbr. (Ri: 40.70%), both used for shade and soil fertilization. Some associated species were used for food (13 species), medicine (17), and timber (seven). Elaeis guineensis Jacq. (Ri: 22.22%), Morinda lucida Benth. (Ri: 55.56%), and Milicia excelsa (Welw.) Berg. (Ri: 51.85%) were the most associated species for food, medicine, and timber, respectively. Conclusions: These results highlight the importance of coffee-based agroecosystems in conserving the flora of the mountainous region of Côte d'Ivoire. Keywords: Coffee, Agrosystems, Montagnes District, Côte d’Ivoire.